Preparation, Characterization and Dye/Heavy Metal Adsorption Properties of Bio-based Composites - Oladipo, Akeem Adeyemi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
Biomagnetic composite based on raw Ferula communis and polyacrylamide (MBFC) was synthesized. The MBFC proved to be an effective and high performance adsorbent for the removal of heavy metals, acidic and basic dyes from simulated effluents by batch and fixed-bed experiments. The morphology, surface and magnetic properties of the as-prepared MBFC were examined by Boehm titration; scanning electron microscope and Fourier transform infrared techniques. The sorption process was optimized via Box-Behnken approach and techno-economic analysis completed using central composite design. The adsorption isotherm, kinetics and parametric behaviors of the pollutants were investigated, and detailed explanation of the results is discussed. The maximum removal efficiencies of the pollutants of 69.3─96.9% were obtained at the optimum operation conditions of 50 mgL─1 initial adsorbate concentration, 100 mg MBFC dose, 360 min contact time, pH 4.0 (acidic dyes) and pH 7.0 (basic dyes and heavy metal ions). The rate-controlling mechanism is discussed in terms of intraparticle diffusion, and the actual step was confirmed by Boyd model. Finally, the efficiency and stability of MBFC were assessed via several regeneration-reuse cycles. Keywords: Bio-based composite; acid dyes; basic dyes; heavy metals; adsorption optimization; modeling; thermokinetic studies.

Ham Ferula communis ve poliakrilamid esaslı biyomanyetik kompozit (MBFC) sentezlenmiştir. MBFC’ın batch ve sabit yatak deneyleriyle ağır metaller, asidik ve bazik boyaların simule atıklarından giderimi için etkili ve yüksek performaslı bir adsorbent olduğu kanıtlandı. Hazırlanmış MBFC’nin morfolojisi, yüzey ve manyetik özellikleri Boehm titrasyonu; taramalı elektron mikroskobu ve Fourier kızılötesi dönüşüm teknikleri ile incelenmiştir. Sorpsiyon süreci Box-Behnken yaklaşımı ile optimize edilmiş ve merkezi kompozit tasarım kullanarak tekno-ekonomik analizi tamamlanmıştır. Adsorpsiyon izotermi, kinetik ve kirletici parametrik davranışlar araştırıldı ve sonuçların detaylı açıklamaları tartışılmıştır. Kirleticiler için maksimum giderim etkinliği, 50 mgL─1 başlangıç adsorbat konsantrasyonu, 100 mg MBFC dozunda 360 dakika temas süresi, pH 4,0 (asidik boyalar) ve pH 7.0 (bazik boya ve ağır metal iyonları) optimum çalışma koşullarında % 69.3─96.9 olarak belirlenmiştir. Orankontrol mekanizması partikül içi difüzyon açısından ele alınmış ve gerçek aşama Boyd modeli ile teyit edilmiştir. Son olarak, MBFC’nin etkinliği ve stabilitesi birçok rejenerasyon-yeniden döngüleri ile değerlendirilmiştir. Anahtar Kelimeler: Biyo-bazlı kompozit; asidik boyalar; bazik boyalar; ağır metaller; adsorpsiyon optimizasyon; modelleme; termokinetik çalşma.
Doctor of Philosophy in Chemistry. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Chemistry, 2015. Supervisor: Assoc. Prof. Dr. Mustafa Gazi.
Keywords: Chemistry; Bio-based composite; acid dyes; basic dyes; heavy metals; adsorption optimization; modeling; thermokinetic studies